2015
DOI: 10.1021/jacs.5b05377
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Alkene Carboaminations Enabled by Oxidative Proton-Coupled Electron Transfer

Abstract: Here we describe a dual catalyst system comprised of an iridium photocatalyst and weak phosphate base that is capable of both selectively homolyzing the N–H bonds of N-arylamides (bond dissociation free energies ~ 100 kcal/mol) via concerted proton-coupled electron transfer (PCET) and mediating efficient carboamination reactions of the resulting amidyl radicals. This manner of PCET activation, which finds its basis in numerous biological redox processes, enables the formal homolysis of a stronger amide N–H bon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 270 publications
(191 citation statements)
references
References 55 publications
5
179
0
4
Order By: Relevance
“…For example, Knowles showed that amides could be oxidized to amidyl radicals and cyclized onto tethered alkenes (Scheme 40). 188 The key PCET step is thought to involve simultaneous deprotonation of 150 by a catalytic phosphate base and electron transfer to photoexcited [Ir III ]*. Following cyclization, alkyl radical 152 can either add to 149 and gain a net hydrogen atom to form 151 , 188 or directly abstract a hydrogen atom from an appropriate donor (hydrogen atom transfer co-catalysis is discussed further in Section 2.4.2).…”
Section: Photoinduced Electron Transfermentioning
confidence: 99%
“…For example, Knowles showed that amides could be oxidized to amidyl radicals and cyclized onto tethered alkenes (Scheme 40). 188 The key PCET step is thought to involve simultaneous deprotonation of 150 by a catalytic phosphate base and electron transfer to photoexcited [Ir III ]*. Following cyclization, alkyl radical 152 can either add to 149 and gain a net hydrogen atom to form 151 , 188 or directly abstract a hydrogen atom from an appropriate donor (hydrogen atom transfer co-catalysis is discussed further in Section 2.4.2).…”
Section: Photoinduced Electron Transfermentioning
confidence: 99%
“…This in turn allows the effective BDFE of any given acid/reductant (or oxidant/base) pair to be varied over an arbitrarily wide range of energies. While not all bases are compatible with all oxidants [30], the use of excited state redox partners as PCET components tends to allow for greater flexibility with respect to which bases may be used [31]. The same principle applies for combinations of acids and reductants.…”
Section: Energetic Characteristics Of Pcet Activationmentioning
confidence: 99%
“…In principle, this remarkable energetic range can enable the rational identification of catalyst systems that are thermodynamically competent to effect homolytic activation of many common organic functional groups that are currently inaccessible using traditional HAT technologies. Even if PCET to a substrate is endergonic, several synthetic examples highlight that even highly endergonic PCET events can be coupled with secondary chemical reactions in catalysis [31][32].…”
Section: Energetic Characteristics Of Pcet Activationmentioning
confidence: 99%
“…Our initial efforts focused on developing a PCET-based protocol for olefin carboamidation (Figure 28) [31]. In this process, PCET activation of N-aryl amide N-H bonds using an Irbased visible-light photoredox catalyst as the oxidant and a weak Brønsted base would furnish reactive amidyls that could undergo intramolecular addition to a proximal olefin.…”
Section: Amidesmentioning
confidence: 99%